Factors Affecting the Cost of Loss of Swine Parts in the Supply Chain of Swine Parts Dealers in Chaiyaphum Province - Imvimon, Thanarat (MBA-KKU Journal, 2023)
Factors affecting the cost of loss of swine parts in the supply chain of swine parts traders. It is an important part of the business of trading swine parts. To analyze the problems that arise in the business in terms of costs. This research therefore has the objectives to study the process in the supply chain of the swine parts trader business. Moreover, the study factors affecting the cost of loss of swine parts in the supply chain of swine parts traders. By collecting data with in-depth interviews from 200 swine parts traders in the fresh market who have been registered as a clean chopping block in Chaiyaphum Province for at least 1 year. Established a process linkage in the supply chain of the swine parts trader business with IDEF by Edraw Max version 9.3 program to analyze the process of the swine parts trader business from upstream activities, midstream as well as downstream activities. The data from the questionnaire was then used for quantitative data analysis with multiple regression analysis. To find factors affecting the cost of swine parts loss. The results of the research revealed that there are 5 activities in the process of the swine parts trader business, namely the activities of receiving swine parts from the slaughterhouse, swine trimming activities for sale, swine parts placement activities for sale, storing swine parts in a freezer tank, swine parts sales activities. Found that transportation costs, management cost and the cost of raw materials is a factor that affects the cost of loss of swine parts. While the cost of storage and cost of expenses it is a factor that does not affect the cost of loss of swine parts in the supply chain of swine parts traders. From such information, entrepreneurs and those involved in the swine parts supply chain are aware of the activities related to the swine parts management in the supply chain. Including understanding the problems and causes that occur and can be used for planning to reduce transportation costs, management cost, cost of raw materials and increase revenue for the swine parts trading business. It is also information that can help government agencies to plan to help swine parts traders operate in a sustainable manner